Effect of thickness and annealing on the optical properties of ZnO membranes in aluminum - Mikhaeel Essa Mansoor; Maysam Shihab Ahmed; Yasir Hussein Mohammed (College of Education for Pure Sciences, 2013)
ABSTRACT In this study 5% Al doped Zinc Oxide for different thickness have been prepared using Atmospheric pressure chemical vapor deposition (APCVD) at 5000C on glass substrates. The effect of thickness and annealing time on optical properties of the films were investigated. From the measurements, It was found  that the transmittance decreases with increasing thickness. On the other hand, the transmittance and the optical gap increases with increasing the annealing time for low thicknesses, While for the higher thicknesses, a little changes were observed.